Embedded system based bangla intelligent social virtual robot with sentiment analysis - Hossain, Md. Ishan Arefin; Hossain, Ismail; Hossain, Md. Yousuf; Banik, Mridul (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.